Water as Divine Mirror in the Poetry of Daud Kamal: El agua como espejo divino en la poesía de Daud Kamal - Zaidi, Ali (Studium, 2020)
Abstract: In the poetry of Daud Kamal, water figures as an image of mercy, as in the Quran, and as a mirror that reflects divine hidden presence. The rock pool evokes the memory of Gandhara and other foundational civilizations born in love and creative ferment. Conversely, the images of drought, heat, and dust symbolize a parched spiritual order. The river, a recurring archetypal image in Kamal’s poetry, represents the fluid self that is subsumed into collective identity to become a poetic distillate of history. Key words: Daud Kamal, water imagery, drought imagery, Pakistani poetry in English, Gandhara civilization, Islamic poetry. Resumen: En la poesía de Daud Kamal (1935-1987), el agua figura como una imagen de misericordia, como en el Corán, y como un espejo que refleja la presencia divina oculta. El estanque evoca la memoria de Gandhara y otras civilizaciones fundamentales nacidas en el amor y el fermento creativo. Por el contrario, las imágenes de sequía, calor y polvo simbolizan un orden espiritual reseco. El río, una imagen arquetípica recurrente en la poesía de Kamal, representa el yo fluido que se subsume en la identidad colectiva para convertirse en un destilado poético de la historia. Palabras clave: Daud Kamal, imágenes de agua, imágenes de sequía, poesía paquistaní en inglés, civilización de Gandhara, poesía islámica.